Rationale and Design of Assessing the Effectiveness of Short-Term Low-Dose Lithium Therapy in Averting Cardiac Surgery-Associated Acute Kidney Injury: A Randomized, Double Blinded, Placebo Controlled Pilot Trial - Sharif, Sairah; Chen, Bohan; Brewster, Pamela; Chen, Tian; Dworkin, Lance; Gong, Rujun (Frontiers in Medicine, 2021)
Background: Burgeoning pre-clinical evidence suggests that therapeutic targeting of glycogen synthase kinase 3β (GSK3β), a convergence point of multiple cellular protective signaling pathways, confers a beneficial effect on acute kidney injury (AKI) in experimental models. However, it remains unknown if GSK3β inhibition likewise mitigates AKI in humans. Cardiac surgery associated acute kidney injury (CSA-AKI) poses a significant challenge for clinicians and currently the only treatment available is general supportive measures. Lithium, an FDA approved mood stabilizer, is the best-known GSK3β inhibitor and has been safely used for over half a century as the first line regimen to treat bipolar affective disorders. This study attempts to examine the effectiveness of short term low dose lithium on CSA-AKI in human patients. Methods/ Design: This is a single center, prospective, randomized, double blinded, placebo controlled pilot study on patients undergoing cardiac surgery with cardiopulmonary bypass. Patients will be randomized to receive a small dose of lithium or placebo treatment for three consecutive days. Renal function will be measured via creatinine (Cr) as well as novel AKI biomarkers. The primary outcome is incidence of AKI according to Acute Kidney Injury Network (AKIN) criteria, and secondary outcomes include receipt of new dialysis, days on dialysis, days on mechanical ventilation, infections within 1 month of surgery, and death within 90 days of surgery. Discussion: As a standard selective inhibitor of GSK3β, lithium has been shown to exert a beneficial effect on tissue repair and regeneration upon acute injury in multiple organ systems, including the central nervous system and hematopoietic system. In experimental AKI, lithium at small doses is able to ameliorate AKI and promote kidney repair. Successful completion of this study will help to assess the effectiveness of lithium in CSA-AKI and could potentially pave the way for large-scale randomized trials to thoroughly evaluate the efficacy of this novel regimen for preventing AKI after cardiac surgery. Trial registration: This study was registered prospectively on the 17th February 2017 at clinicaltrials.gov (NCT03056248,https://clinicaltrials.gov/ct2/show/NCT03056248?term=NCT03056248&draw=2&rank=1).